Lecturer’s Personal Branding in the Digital Era: Building Good Reputation and Positive Image through Social Media - Nur Fitria, Tira (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
This research describes the lecturer’s branding in the digital era to build a good reputation and positive image through social media. This research uses library research. The analysis shows that the digital era and technological developments have provided numerous benefits, including the ability to build and promote personal branding on various social media platforms. Social media platforms and personal websites/blogs can be used to create a personal brand and establish an online identity. Academic and publication portals such as Google Scholar, Sinta, ResearchGate, Orcid.org, and others can be utilized to promote the lecturer’s scientific works and establish a professional image and social ties within the community. Therefore, personal branding is essential for lecturers to establish a strong self-image and a directed career, allow for a wider public reach, and focus on goals and relationships with the Tri Dharma of Higher Education. Besides, the other benefits of a lecturer’s branding include building confidence, increasing credibility, building academic branding for an institution, becoming the face of the world of national higher education, expanding the network and relationships, developing capabilities and skills, having academic achievements, being active on social media, becoming a friendly and open lecturer, develop capabilities and skills, and increasing income. Critical factors for personal branding include creating knowledge, building trust, creating a reputation, and influencing perception. By focusing on these aspects, lecturers can create a good reputation and positive image to contribute to their career development.